2013
DOI: 10.1111/ejh.12209
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular and atrial diastolic function using two‐dimensional (2D) strain imaging in patients with β‐thalassemia major

Abstract: B-thalassemic major patients with preserved left ventricular systolic function had impaired left atrial function at the longitudinal axis and left ventricular function at the radial axis. The new echo markers have better prognostic value than the traditional echo indexes in detecting latent diastolic dysfunction in β-thalassemia major, earlier than E/E' ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Also for quantification of segmental and global circumferential myocardial deformation, from the short‐axis view, the left ventricle was divided into six segments (mid‐anteroseptum, mid‐anterior, mid‐anterolateral, mid‐inferolateral, mid‐inferior, and mid‐inferoseptum). Based on the entire short‐axis contour at papillary muscle level, we made the calculations on these six segments …”
Section: Methodsmentioning
confidence: 99%
“…Also for quantification of segmental and global circumferential myocardial deformation, from the short‐axis view, the left ventricle was divided into six segments (mid‐anteroseptum, mid‐anterior, mid‐anterolateral, mid‐inferolateral, mid‐inferior, and mid‐inferoseptum). Based on the entire short‐axis contour at papillary muscle level, we made the calculations on these six segments …”
Section: Methodsmentioning
confidence: 99%
“…Different studies have shown an early compromise of diastolic function in young patients with beta thalassemia and marked Fe overload (ferritin > 2000 ng/mL). Kostopoulo et al observed an increase in LA size and a decrease in the active and passive ejection fraction of the left atrium compared with a control population (19), and in the same sense, a decrease in atrial strain has been observed during the reservoir phase (20). The compromise of the LA function could occur both as a consequence of the increase in its afterload due to the increased LV rigidity, as well as its intrinsic compromise by Fe deposits in the atrial myocardium.…”
Section: Discussionmentioning
confidence: 94%
“…These methods have already been evaluated specifically in patients with β-thalassemia, demonstrating an important correlation even with cardiac damage secondary to iron overload 14 . They also present a better prognostic value for diastolic dysfunction in this group of patients than parameters evaluated in traditional echocardiography 15 . The use of these new techniques in heterozygous patients still needs to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%